Alliin, capsaicin, and gingerol attenuate endoplasmic reticulum stress-induced hepatic steatosis in HepG2 cells and C57BL/6N mice. (August 2022) - Yun, Ye-Rang; Lee, Ji-Eun
Graphical abstract: Highlights: Kimchi active components inhibit hepatic steatosis in ER stress-induced HepG2 cells. Kimchi active components inhibit hepatic steatosis through the LXRα/AMPK pathway. Kimchi components inhibit hepatic steatosis in ER stress-induced C57BL/6N mice. Kimchi active components could be used to treat ER stress-induced disease. Abstract: Recently, food ingredients that suppress endoplasmic reticulum (ER) stress have been studied for their potential application in non-alcoholic fatty liver disease (NAFLD) treatment. Kimchi active components can suppress ER stress-related markers; therefore, we investigated the inhibitory effects of alliin, capsaicin, and gingerol on tunicamycin-induced hepatic steatosis in HepG2 cells and C57BL/6N mice by measuring ER stress-, lipogenesis-, and inflammation-related gene expression, and lipid accumulation. Alliin, capsaicin, and gingerol efficiently decreased triglyceride content and all gene expression in tunicamycin-induced cells without cytotoxicity. Alliin, capsaicin, and gingerol inhibited lipogenesis-related gene expression that increased following T0901317 treatment and decreased following AICAR treatment. Furthermore, alliin, capsaicin, and gingerol decreased serum lipid and hepatic lipid levels and all marker expression in tunicamycin-induced mice without hepatic toxicity. They also inhibited lipid accumulation in tunicamycin-induced mice. Collectively, kimchi active components prevented triglyceride accumulation and hepatic steatosis in ER stress-induced HepG2 cells and C57BL/6N mice.